Teacher Education Programmes and Their Contribution to Student Teacher Efficacy in Classroom Management and Pupil Engagement. Issue 2 (3rd March 2016) - Christophersen, Knut A.; Elstad, Eyvind; Turmo, Are; Solhaug, Trond
Abstract : This study focuses on how different educational programmes contribute to student teachers efficacy for classroom management and their abilities to provide learning opportunities and good classroom outcomes. Data were gathered from 491 student teachers attending different teacher education programmes in Norway and analysed via structural equation modelling. The results revealed the following: (1) problem behaviour in the classroom has a negative effect on student teacher efficacy, (2) students' perceptions of the integration of pedagogic knowledge and practice supports students' efficacy beliefs, (3) support from supervisors contributes positively to student teachers' efficacy beliefs, and (4) student teachers in university college programmes for primary school teaching report higher teacher efficacy than students in university programmes for secondary school teaching.